2014
DOI: 10.1002/biot.201400023
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the productivity of recombinant Escherichia coli for limonene formation from glycerol in minimal media

Abstract: The efficiency and productivity of cellular biocatalysts play a key role in the industrial synthesis of fine and bulk chemicals. This study focuses on optimizing the synthesis of (S)-limonene from glycerol and glucose as carbon sources using recombinant Escherichia coli. The cyclic monoterpene limonene is extensively used in the fragrance, food, and cosmetic industries. Recently, limonene also gained interest as alternative jet fuel of biological origin. Key parameters that limit the (S)-limonene yield, relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 50 publications
(63 reference statements)
4
111
0
Order By: Relevance
“…The present work showed that geraniol production was increased to 48.5 ± 0.9 mg L −1 by engineering tCaGES and the foreign genes mentioned above. The geraniol yield of this study is higher than those in transgenic tobacco and yeast; also, parallel to or higher than the yields of other terpenes production in metabolically engineered microorganisms [23,32,39,40,42]. Recently it has been demonstrated that deletion of YjgB, an endogenous dehydrogenase responsible for geraniol loss in E. coli MG1655, will increase geraniol production to 182.5 mg L −1 [38].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The present work showed that geraniol production was increased to 48.5 ± 0.9 mg L −1 by engineering tCaGES and the foreign genes mentioned above. The geraniol yield of this study is higher than those in transgenic tobacco and yeast; also, parallel to or higher than the yields of other terpenes production in metabolically engineered microorganisms [23,32,39,40,42]. Recently it has been demonstrated that deletion of YjgB, an endogenous dehydrogenase responsible for geraniol loss in E. coli MG1655, will increase geraniol production to 182.5 mg L −1 [38].…”
Section: Discussionmentioning
confidence: 57%
“…In addition, the fed-batch fermentation was proved to increase the yields of other terpenes [23,39,40,42]. Thus, this study will be an alternative to selectively produce geraniol in engineered E. coli, together with other metabolic engineering methods such as balancing the whole biosynthetic pathway and using fed-batch fermentation.…”
Section: Discussionmentioning
confidence: 96%
“…Limonene fermentation using glycerol as a carbon source has also been explored [44 ]. Glycerol provides a prolonged growth and production phase, achieving titers as high as 2.7 g/L (Table 1) [44 ].…”
Section: Terpenesmentioning
confidence: 99%
“…Glycerol provides a prolonged growth and production phase, achieving titers as high as 2.7 g/L (Table 1) [44 ].…”
Section: Terpenesmentioning
confidence: 99%
“…Considering the isoprenoid bioprocesses with direct contact and internal removal listed in Table 1 it is notable that only laboratory-scale systems with total reaction volumes typically below 10 L have been published and that most publications describe a proof-of-concept without further investigating product purification from the receiving phase. Exceptions are the distillation of limonene produced by recombinant E. coli from diisononyl phthalate [107], the purification of artemisinic acid from isopropyl myristate [65], and a stirred-tank reactor operated in continuous cultivation mode with a continuous recovery of the product α-santalene and regeneration of the extractive solvent dodecane [78]. On the shaking flask scale the recovery of bisabolene from the organic phase and its purification and subsequent chemical treatment have been described [67].…”
Section: Two-liquid Phase Bioprocessesmentioning
confidence: 99%